Guanidines Conjugated with Cell-Penetrating Peptides: A New Approach for the Development of Antileishmanial Molecules - João Victor Marcelino de Souza; Natalia C. S. Costa; Maria C. O. Arruda Brasil; Luana Ribeiro dos Anjos; Renata Priscila Barros de Menezes; Eduardo Henrique Zampieri; Jhonatan Santos de Lima; Angela Maria Arenas Velasquez; Luciana Scotti; Marcus Tullius Scotti; Marcia A. S. Graminha; Eduardo R. Pérez Gonzalez; et al. (Molecules)
Leishmaniasis is a neglected tropical disease caused by a protozoan of the genus Leishmania, which has visceral and cutaneous forms. The symptoms of leishmaniasis include high fever and weakness, and the cutaneous infection also causes lesions under the skin. The drugs used to treat leishmaniasis have become less effective due to the resistance mechanisms of the protozoa. In addition, the current compounds have low selectivity for the pathogen, leading to various side effects, which results in lower adherence to treatment. Various strategies were developed to solve this problem. The bioconjugation between natural compounds with antimicrobial activity and cell-penetrating peptides could alleviate the resistance and toxicity of current treatments. This work aims to conjugate the cell penetration peptide TAT to the guanidine GVL1. The GVL1-TAT bioconjugate exhibited leishmanicidal activity against Leishmania amazonensis and Leishmania infantum with a high selectivity index. In addition, the bioconjugate was more active against the intracellular enzyme CPP than the individual compounds. This target is very important for the viability and virulence of the parasite within the host cell. Docking studies confirmed the higher interaction of the conjugate with CPP and suggested that other proteins, such as trypanothione reductase, could be targeted. Thus, the data indicated that guanidines conjugated with cell-penetrating peptides could be a good approach for developing antileishmanial molecules.